Adaptation of thermal comfort in naturally ventilated students residential college in tropical climates of Malaysia - Khamis, Nur Syahirah Nissa; Zainal, Rozlin; Musa, Sharifah Meryam Shareh; Kasim, Narimah (2021)
The climate in tropical regions was affecting the level of thermal comfort of the individual while accommodating the residential buildings. Residential buildings especially student residential colleges in Malaysia were mainly build depending on natural ventilation systems as a tool to facilitate comfort in their daily life without the consent of the mechanical ventilation system such as air conditioners. This study has been done by distributing a questionnaire to the occupants who live in the naturally ventilated residential college and conducting an interview series with a college management officer to prove and validate the data collected throughout the study. The result of the study shows that students most likely will change their behavior due to the level of heat stress in the dormitory. Statistics from the data collected shown that students were very relying on the support of the mechanical ventilation system and they are also keener towards wearing a thinner and comfortable clothing material as it will help them to reduce the heat discomfort throughout the day. This study also shows a positive correlation analysis between the relationship of low ventilation flow and the level of indoor thermal comfort. This situation is regarded as the environmental factors that play important roles in the level of thermal comfort in a residential building, especially in tropical climates.